2016
DOI: 10.1016/j.jhep.2016.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Multivariate metabotyping of plasma predicts survival in patients with decompensated cirrhosis

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
68
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(74 citation statements)
references
References 54 publications
6
68
0
Order By: Relevance
“…Metabolomics studies, while only conducted in small cohorts to date, have showed that plasma metabolites including tyrosine may have high discriminatory value in predicting short-term mortality in both alcoholic hepatitis and decompensated cirrhosis. 35,36 C-reactive protein, frailty indices, and even cardiac function markers have also shown promise in this area. 37 Given the rising prevalence of NASH, some of these markers of more systemic dysfunction might be valuable in gauging the overall health of a listed individual.…”
Section: Discussionmentioning
confidence: 99%
“…Metabolomics studies, while only conducted in small cohorts to date, have showed that plasma metabolites including tyrosine may have high discriminatory value in predicting short-term mortality in both alcoholic hepatitis and decompensated cirrhosis. 35,36 C-reactive protein, frailty indices, and even cardiac function markers have also shown promise in this area. 37 Given the rising prevalence of NASH, some of these markers of more systemic dysfunction might be valuable in gauging the overall health of a listed individual.…”
Section: Discussionmentioning
confidence: 99%
“…More commonly, MS-based methods have shown elevations in specific serum bile acids in human liver cirrhosis [128,132,135], together with fluctuations in a broad range of urinary steroids [141]. Another common finding were alterations in serum phospholipids in both human liver cirrhosis [135,139,140] and in animal models [169,170,172]. In both the human and animal model investigations, perturbations in metabolic intermediates, akin to those revealed by NMR, have also been described.…”
Section: Uplc-qtofmsmentioning
confidence: 99%
“…LPC concentrations negatively correlated with the circulating markers of cell death, M30 and M65. Therefore, metabolomic phenotyping ("metabotyping") was said to accurately predict mortality in decompensated cirrhosis, due to LPC and amino acid metabolism dysregulation that reflected hepatocyte cell death [140]. Using LC-MS, a Chinese group profiled 43 steroids in the urine of HV (21), LC (21), and HCC (28) relative to urinary creatinine.…”
Section: Fibrosis and Cirrhosismentioning
confidence: 99%
“…Most of the studies published to date are relatively small pilot studies, but larger, externally validated studies are emerging more recently: the study by McPhail et al demonstrating external validation in two independent cohorts of a model for the prediction of survival in decompensated liver cirrhosis patients is a landmark (McPhail et al, 2016). …”
Section: Discussionmentioning
confidence: 99%